EXTENSION OF LINEAR ISOTHERM REGULARITY TO LOWER DENSITY RANGE (Journal of Sciences, Islamic Republic of Iran)
The general equation of state which was found for dense fluids, both compressed liquids and dense supercritical fluids, namely "Linear Isotherm Regularity," is extended to the lower density range, specifically for densities lower than the Boyle density. This new equation of state which is called "ELIR" is shown to be compatible with the equations of state based on statistical-mechanical theory, although ELIR gives a more accurate density at high pressures. This equation of state has been tested with experimental data for different fluids (Ar,N , O , CO, CH , C H , CH 0H ,H ) for both vapor and compressed liquid phases. The ELIR is able to predict the critical isotherm and also both of the coexistence phases at equilibrium can be expressed by a single ELIR equation of state